2024
DOI: 10.1002/adom.202302257
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Engineered Methylammonium Lead Bromide Single Crystals: A Platform for Fluorescent Security Tags and Photodetector Applications

Somnath Mahato,
Magdalena Tamulewicz‐Szwajkowska,
Sudarshan Singh
et al.

Abstract: Surface/interface engineering of methylammonium lead bromide (MAPbBr3) single crystals (SCs) is crucial for carrier generation/recombination, separation, and transportation, thereby enabling superior optoelectronics. Herein, a surface‐engineered crystallization technique is presented in which a thin polycrystalline MAPbBr3 layer is in situ grown on the surface of bulk mm‐sized MAPbBr3 SCs. The growth direction and the atomic distribution of both the polycrystalline surface layer and the single crystalline core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…In this study, we successfully grew high-quality transparent millimeter - sized MAPbBr 3 SCs, resulting in a bright green emission from the surface upon exposure to UV light. The detailed synthesis process was described in the previous work . Cathodoluminescence (CL) images demonstrated that THF-0.4M crystals exhibited enhanced luminescence signals, and photoluminescence (PL) measurements revealed a 10-fold increase in PL intensity compared to Control-1M MAPbBr 3 SCs.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we successfully grew high-quality transparent millimeter - sized MAPbBr 3 SCs, resulting in a bright green emission from the surface upon exposure to UV light. The detailed synthesis process was described in the previous work . Cathodoluminescence (CL) images demonstrated that THF-0.4M crystals exhibited enhanced luminescence signals, and photoluminescence (PL) measurements revealed a 10-fold increase in PL intensity compared to Control-1M MAPbBr 3 SCs.…”
mentioning
confidence: 99%
“…Specifically, the THF-0.4M crystal demonstrates an increase of 2.4 times in comparison to the Control-1M crystal. The increase in RLY at cryogenic temperatures is linked to the increase of the modest quantum yield (2 times) and conductivity (almost 2 times) of the bulk crystals . The latter is strongly related to the transfer efficiency in the scintillation mechanism process .…”
mentioning
confidence: 99%
See 3 more Smart Citations